The Influence of Net Interest Margin, Non-Performing Loans, and Capital Adequacy Ratio on the Stock Prices of KBMI 4 Banks - Trihatmoko, Huda; Ridarmelli, Ridarmelli; Saputra, Kevin Arya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine the influence of net interest margin, non-performing loans, and capital adequacy ratio on the stock prices of banks classified as KBMI 4, which are listed on the Indonesia Stock Exchange (IDX) for the period from 2014 to 2021. The research employs a purposive sampling method, resulting in a sample of four banking companies. Multiple linear regression analysis is utilized to analyze the data, with the assistance of the Eviews 12 software. The findings indicate that the capital adequacy ratio positively affects banking stock prices, whereas the net interest margin negatively impacts them. Conversely, non-performing loans do not exhibit a significant effect on the stock prices of these banks.